Molecular polymorphism of Plasmodium vivax Duffy binding protein domain II from Nicaragua, and global diversity patterns - Ortega-Monroy, René; Tomasini-Ovilla, Hugo A.; Santillan-Valenzuela, Frida; Montoya, Alberto; Gonzalez-Ceron, Lilia (Frontiers in Malaria, 2025)
BackgroundPlasmodium vivax Duffy binding protein domain II (PvBDPII) is a promising vaccine candidate due to its crucial role in reticulocyte invasion. However, polymorphism is a concern as it may confer evasion of blocking antibodies. In this study, nucleotide and protein polymorphism were analyzed in parasites collected during a decline in malaria cases in Nicaragua.MethodsGenomic DNA was extracted from P. vivax blood samples obtained from symptomatic patients in Nicaragua during 2012–2013. The PvdbpII gene was amplified and sequenced, and genetic structure, genealogical relationships, and amino acid polymorphism were analyzed. For comparison and to elucidate global variation of this gene, homologous sequences from other geographical regions were included.ResultsSixty-three consensus sequences from Nicaragua were obtained, revealing 12 non-synonymous mutations and 6 haplotypes (Hd=0.704). Nucleotide diversity was lower (π=0.0044) than in other endemic regions. The Z test of selection (dN/dS) was positive (3.17; p < 0.001), similar to parasite populations worldwide (Latin America, Middle East, Asia, Southeast Asia, Africa, Papua New Guinea). Network analysis revealed that Nicaraguan pvdbpII haplotypes differed by 3–12 mutational steps. High-frequency haplotypes from six other Latin American countries were shared, showing signs of diversification and limited population structure. Five Nicaraguan haplotypes corresponded to the 10 most frequent globally. Haplotypes defined solely by amino acid changes at positions 417, 437, and 503 were of the Sal-I type (NWI), NWK, and KRK. These, along with KRI, were shared across most regions at varying frequencies. Based on these variations, two main divergent groups were identified.ConclusionsThe low diversity observed in pvdbpII suggests a population contraction aligning with the decline of malaria cases in Nicaragua during the sampling period. The PvDBPII haplotypes found may represent those best adapted in Nicaragua and in other endemic regions globally, encompassing both Sal-I-related and divergent types. It would be beneficial to assess the ability of the most frequent and persistent haplotypes to elicit phenotype-transcending immunity, which is critical for the development of a multicomponent vaccine and for monitoring its effectiveness.